Superordinate identities and self-transcendent emotions: Longitudinal study in Spain and Chile - Wlodarczyk, Anna; Méndez, Lander; Cusi, Olaia; Telletxea, Saioa; Mendia, Jara; Briceño, Mauricio; Delgado, Daniela; Balbontín, Francisca; Lecaros, Alexandra; Páez, Darío (Frontiers in Psychology, 2022)
Recent studies suggest that identification with all humanity (IWAH), apart from being related to universalistic values, could also be related to self-transcendent emotions (STE). In this scenario, the general objective of this cross-cultural longitudinal study is to examine the relationship between identification with proximate categories (i.e., community and country) and superordinate one (all humanity), and their association with positive self-oriented and STEs during a traumatic global phenomenon such as COVID-19 pandemics. Additionally, we explore variations regarding the patterns of those associations in different cultural contexts (Chile and Spain) and examine whether they change among two different time points (T1–T2). The total sample was composed of 403 participants, of whom 224 were residents in Chile (M = 39.25, SD = 12.56; range 18–71 years; 49.6% women) and 179 were residents in Spain (M = 36.35, SD = 12.12; range 18–68 years; 59.8% women). Data collection was carried out in September (T1) and November (T2) 2020, through online surveys administered via Survey Monkey® platform. Overall, results show, as expected, greater identification with proximate categories rather than superordinate ones, and an association between STEs and IWAH, but also with national and community identification. IWAH, but not STEs decreased significantly (T1–T2) in both countries. Thereafter, these emotional and behavioral responses decline as a symptom of growing fatigue with the pandemic situation, and also reflect a shift from broader to more local concerns. Analysis regarding comparisons between countries indicated higher levels of identification with community and with all humanity in Spain and with country in Chile. The results are discussed in the context of new developments in studies on IWAH.